REACTION OVER EMPLOYEES TURNOVER INTENTION WHICH INFLUENCED BY CAREER DEVELOPMENT, WORK LOAD AND COMPENSATION AT PT XYZ - Tiopan Silitonga, Rongguan Selamat; Noviandy Aulia, Irfan (Dinasti Publisher, 2020)
This research intend to examined that influence which came from career development, workload and compensation towards turnover intention at PT XYZ's employees. Research population were employees from PT XYZ JATA 2 Area, which amounting to 378 employees, which sample amounted to 195 respondents (by Slovin 5% error tolerance). Data analysis method by multiple linear regression analysis to examined several hypothesis. Those results that earned from this research, such as : 1) There had strongly influence between career development to turnover intention; 2) There has none reaction which occurs from workload towards turnover intention; 3) There had no impact between compensation and turnover intention; 4) There had simultaneously reacted between career development, workload, and compensation against turnover intention.